Combining RNA interference and biological control for the sustainable control of stink bugs in Brazilian soybean fields - Castellanos, Nathaly Lara (2019)
Soybean is the most commercialized agricultural product in Brazil, and accounts for an important share of its GDP. In recent years, the sustainability of soybean production has been threatened by the over-reliance on conventional pesticide sprays as the only tool for insect pest control. The Neotropical brown stink bug, Euschistus heros, is the main target of those insecticide applications and an important soybean pest in South America. For a transition towards sustainability of E. heros control, the development of alternative control strategies that can be easily integrated into Integrated Pest Man- agement (IPM) programs are required. Therefore, the aim of this PhD dissertation was to investigate the potential for combining RNAi technology and biological control for the sustainable control of E. heros in Brazilian soybean fields. Insecticide resistance is one of the main concerns when using insecticides as a single management tool. To under- stand the risks and to determine possible mechanisms of resistance to neonicotinoids in E. heros, two imidacloprid resistant strains were selected under the laboratory condi- tions. The first strain derived from a laboratory susceptible strain, while the other derived from a field population diagnosed with control failure. Both strains achieved significant resistance levels, but the field derived strain required only six generations of selection in comparison to the 13 generations required by the laboratory-derived strain. The resis- tance to imidacloprid was linked with the enhanced activity of cytochrome P450 in both imidacloprid-resistant strains. But the higher activity of these enzymes was associatedAbstract with severe fitness costs that could delay the occurrence of imidacloprid-resistant strains if preventive management practices are implemented. Among sustainable control meth- ods, biological control using the egg parasitoid Telenomus podisi has the potential not only to suppress E. heros populations, but also to delay the evolution of insecticide resis- tance. Development of rearing protocols that ensure the sustained quality and efficiency of released insect agents in field is an important factor for the success of biological con- trol programs. Thus, we investigated whether a fluctuating thermal regime can be better for the mass rearing of T. podisi than the constant regime that is currently used. The fluctuating thermal regime was more suitable for mass-rearing than the constant regime, as demonstrated by the increased fitness and reduced estimated costs for production. These findings suggest that parasitoid wasps reared under fluctuating regime tolerate better fluctuating temperatures that normally occur both during transport and in agricul- tural systems, which will increase the quality and productivity of mass-reared T. podisi for inundative releases. The success of augmentative biological control programs using T. podisi against E. heros will depend on the integration with other sustainable manage- ment approaches, since it is difficult to control pest populations using biological control alone. In this regard, RNA interference (RNAi) offers a selective and environmentally safe alternative for the control of this pest. Injection of target genes encoding proteins that are essential for growth and development caused significant mortality and suppres- sion of the target transcript. dsRNA was also administered by feeding the insects with the artificial diet containing different forms of dsRNA for delivery: naked dsRNA, dsRNA with EDTA and dsRNA encapsulated in liposomes. Oral delivery of naked dsRNA resulted in lower RNAi efficiency, evidencing no clear mortality scores probably due to dsRNA degradation by the salivary secretions of E. heros. Furthermore, the use of EDTA and lipid-based nanoparticles improve the oral delivery of dsRNA. These formulations could have a great potential for developing novel strategies for pest management of stink bugs based on RNAi preventing the dsRNA of being degraded enzymatically by the saliva. The successful integration of RNAi-based insecticides and biological control will depend on the lack of adverse effects of RNAi to the parasitoid T. podisi. Consequently, the potential routes of exposure and hazards were assessed. Parasitoid wasp can be ex- posed to RNAi-based insecticides directly via consumption of pollen and nectar in theAbstract adult life or indirectly during the development inside host eggs. In addition, ingestion of specific dsRNA resulted in reduced fitness and target gene expression, demonstrating that T. podisi adults can be physiologically exposed to insecticidal dsRNA. No adverse effects were observed in the survival, development or parasitism of T. podisi treated with dsRNAs targeting E. heros genes. Moreover, the expression levels of potential off- target genes tested were not downregulated. Although there is still much work needed to translate the research outputs of this PhD thesis into practical IPM tools for soybean production. These data support the possibility of combining RNAi-based insecticides and biological control using the parasitoid T. podisi inside IPM programs to improve the sustainability of E. heros control in the future. Keywords: Euschistus heros. Telenomus podisi. RNAi. Insecticide resistance. Fluctu- ating thermal regimes.